Web-Based Inventory Management Application Using PHP and MySQL - Herlina, Herlina; Hamied, Zamzam Rachman; Hidayat, Rahmad; Mutakin, Asep Hilmi; Lestari, Ninik Sri; Hermawaty, Hermawaty; Fadriani, Hetty (International Journal of Computer and Information System (IJCIS), 2024)
Abstract— In this era of computerization, the human need for information drives the rapid development of technology in the fields of information and telecommunication technology. With the current developments in information technology, data processing can be done easily. Manual data entry has several drawbacks, including the potential for errors in writing and reading, and it is also prone to loss or damage. From the aforementioned issues, the author has developed a web-based inventory management information system to facilitate the management of stock data. The purpose of creating this inventory management system application is to help integrate data properly and enable easy and accurate data processing. The development of this system uses the waterfall system design method, which can help in the creation of the system by following a sequential process. This method is carried out starting from the stages of requirement analysis, system and software design, implementation, system testing, and maintenance. The design tool uses UML (Unified Modeling Language) to create use case diagrams, activity diagrams, and class diagrams. The data collection system uses observation, interviews, documentation, and literature study methods, and employs the PHP programming language and MySQL as the database. Based on the testing results, this information system can process incoming and outgoing item data, store data, and generate reports.